2007
DOI: 10.1163/156855507780378258
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in synthesis of ferrocenyl dendrimers and their application in anion recognition

Abstract: Abstract-Anion recognition has attracted increasing attention due to the importance in biology and environment protection. Ferrocenyl dendrimers represent a type of novel competitive candidate for anion recognition owing to the combination of merits with ferrocene and dendrimer. This review focuses on recent progress in synthesis of ferrocenyl dendrimers and their application in anion recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…A cyclic receptor (Figure 4) was expected to dimensionally complement and encapsule the anions in its cavity. 30 N,N′-Bisethoxyethane- [12]amideferrocenophane (11) has a hygrophilic cyclic amine structure. However, unexpected results showed that 11 had low selectivity in recognition, which may be attributed to the flexibility of the amine loop.…”
Section: Molecular Recognition Based Onmentioning
confidence: 99%
See 2 more Smart Citations
“…A cyclic receptor (Figure 4) was expected to dimensionally complement and encapsule the anions in its cavity. 30 N,N′-Bisethoxyethane- [12]amideferrocenophane (11) has a hygrophilic cyclic amine structure. However, unexpected results showed that 11 had low selectivity in recognition, which may be attributed to the flexibility of the amine loop.…”
Section: Molecular Recognition Based Onmentioning
confidence: 99%
“…However, unexpected results showed that 11 had low selectivity in recognition, which may be attributed to the flexibility of the amine loop. 31 A ferrocene bis(triazole) macrocycle (12) was synthesized by Eglinton coupling of an acyclic bis(alkyne) precusor. With the diyne unit in its structure, 12 showed rigid geometry in the macrocycle.…”
Section: Molecular Recognition Based Onmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, a number of comprehensive articles focusing on ferrocene‐based derivatives with azobenzene units have been reported . But few articles provide a detailed account of the development of these kinds of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers have potential applications in the fields of medicine, additives, coatings, composites, catalysis, etc. [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%